ANALYSIS OF COVID-19 CONTAMINATION AND DEATHS CASES IN BRAZIL ACCORDING TO THE NEWCOMB-BENFORD - CARMO, Carlos Roberto Souza; CANEPPELE, Fernando de Lima; NUNES, Fábio Caixeta (Brazilian Journal of Biometrics, 2021)
The use of the Newcomb-Benford Law in assessing the quality of health and / or epidemiological information systems can allow relevant decisions to be made to improve these systems. In this context, this research aimed to carry out an assessment of the conformity of the information regarding the number of cases of contamination and deaths by COVID-19 in Brazil according to the Newcomb-Benford Law, from the moment of the occurrence of the first case of the disease and from the first death by COVID-19 in the country until the month of September 2020. With the aid of descriptive statistics and the use of metrics related to the Z test and the mean absolute deviation it was possible to observe that, both from a national and longitudinal perspective as for the transversal-state perspective, the quantitative data referring to the cases of contamination by the coronavirus and the deaths that occurred as a result of COVID-19 did not present the expected behavior according to the Newcomb-Benford Law. Due to the lack of conformity in relation to the Newcomb-Benford Law, it is suspected that some level of conformity specific to this type of data has occurred, in the Brazilian context, since there are already studies that suggest the existence of proper levels of conformity for certain types of data.